Archaeological Discoveries in the Ancient State of Lagash: Results from the Italian Excavations at Tell Zurghul/Nigin in Southern Iraq - Nadali, Davide; Polcaro, Andrea (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2018)
The Italian archaeological project at Tell Zurghul is a joint archaeological expedition of Sapienza Università di Roma and the Università degli Studi di Perugia and started working at the site in 2015; three seasons of excavation have been conducted with three operations (Area A, Area B, and Area D) and a survey on the western edge of the site (Area C) (Figure 1). More recently, fieldwork also encompassed the execution of geological soundings in different spots of the site to verify the nature and composition of the sediments, in relation to the presence of water that extensively characterised and affected the ancient and contemporary landscape of the region.